Self-Declare on Micro and Small Restaurant in Supporting Muslim-Friendly Tourism Industry - Eka Destyana, Muthia; Setyowati, Ro'fah; Ayu Musyafa, Aisyah; Shifa Akhsanty, Allya (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Halal logo for business actors, especially food business is a liability as regulated in the Halal Product Guarantee Law. Since the enactment Job Creation Law, regulations on halal certification have been changed and renewed. Self-declare is the issues that raised pros and cons. The purpose of this study is evaluate Self-declare on micro and small restaurants in supporting muslim-friendly tourism industry. In discussing the topic, the research using normative juridical method with materials from primary data and secondary data. The results show that Self-declare is not consistent with the substance of the Halal Product Guarantee law. Practically, Self-declare has a positive impact for economic benefits because the process of applying halal certification is short and easy for restaurant businesses. Thus, the Self-declare concept supports the development of the halal tourism industry in Indonesia. It is necessary to complemented by supervision system to maintain the quality and objectives of halal certification.